(untitled) (Research, Society and Development, 2023)
Motor and praxis disorders, although are not diagnostic criteria for Autism Spectrum Disorder (ASD), are present in most autistic children, and alterations in gross motor coordination, praxis, tonus, balance, postural control and motor planning may occur. Much research has been developed investigating cognitive, social and emotional skills of children with ASD, while motor aspects have received less scientific attention. Thus, this study aimed to evaluate the psychomotor function of children with ASD who practice hippotherapy. This is a cross-sectional study with quantitative analysis. The study included 9 caregivers of children aged 4 to 11 years, diagnosed with ASD, practitioners of hippotherapy for at least 6 months, who answered the Childhood Autism Rating Scale - CARS. With the 9 children of these caregivers, the Motor Development Scale was applied, seeking to investigate motor performance in balance, body scheme, spatial organization, temporal organization/language, fine motor skills and global motor skills. No significant relationship was found between the degree of autism and the level of motor delay, but there are indications of a greater influence on the components of the body schema and temporal organization/language. All evaluated children had some degree of dyspraxia. A greater relationship was found between the duration of equine therapy and the development of fine motor skills and balance. All evaluated children performed was below the expectations for their chronological age, reinforcing the importance of psychomotor practice in their treatment, such as hippotherapy.